SERVICE QUALITY ANALYSIS FOR CUSTOMER JOURNEY EXPERIENCE IMPROVEMENT AT TERMINAL 3 SOEKARNO-HATTA INTERNATIONAL AIRPORT (The Indonesian Journal of Business Administration, 2019)
Terminal 3 (T3) owned by PT Angkasa Pura II (AP II) at Soekarno-Hatta International Airport is a high-class airport for serve domestic and international passengers. AP II realize the importance of service quality by regularly monitoring the development of customer satisfaction to encourage continuous service improvement. In this research, the orientation of customers at T3 Soekarno-Hatta International Airport will be assessed based on experience of interaction with facilities and services that have been used. To achieve the objectives, the research will apply qualitative and quantitative by Service Quality (SERVQUAL) methods.Analysis of the T3 Soekarno-Hatta International Airport to determine external and internal conditions that have an impact on the existing business, evaluation uses SWOT analysis. Service quality to the level of customer satisfaction in term of tangible, reliability, responsiveness, assurance, and empathy at T3 Soekarno-Hatta International Airport have positive correlations. With notes, found three partial gaps data in the SERVQUAL dimensions indicators. The dimensions that has the greatest value to the creation of customer satisfaction at T3 Soekarno-Hatta International Airport is tangible dimension.Based on the findings of the research, suggestions are made to relevant parties at T3 Soekarno-Hatta International Airport through strategic improvement namely service improvement program, facility improvement program, and activity & entertainment improvement program.Keywords: Service Quality, T3 Soekarno-Hatta International Airport, Customer, Expectation, Performance.